Effects of long-term synbiotic supplementation in addition to lifestyle changes in children with obesity-related non-alcoholic fatty liver disease - Çakır, Murat; Aksel İşbilen, Ayşe and Eyüpoğlu, İlker and Sağ, Elif and Örem, Asım and Mazlum Şen, Tuğba and Kaklıkkaya, Neşe and Kaya, Gülay (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: We aimed to analyze the efficiency of a novel treatment approach, long-term synbiotic supplementation, in addition to lifestyle changes in children with non-alcoholic fatty liver disease (NAFLD). Materials and Methods: The study included children with NAFLD (n=28) and a healthy control group (n=30). Children with NAFLD were given 1 capsule/day of synbiotics. Anthropometric parameters; biochemical analysis, including ethanol, tumor necrosis factor-α (TNF-α), total oxidant status (TOS) and anti-oxidant status (TAS), zonulin, and fecal calprotectin; and ultrasonographic examination were performed at baseline and 4 months later. Results: The grade of fatty liver was decreased (≥1 grade) in 19 of the 28 patients (67.8%) after synbiotic supplementation. Total cholesterol, low-density lipoprotein (LDL) levels, TNF-α, C-reactive protein (CRP), and ethanol were significantly decreased, and TAS levels were significantly increased at the end of treatment (p Conclusion: Synbiotic supplementation in addition to lifestyle changes is effective in children with NAFLD. Cite this article as: Çakır M, İşbilen AA, Eyüpoğlu İ, et al. Effects of long-term synbiotic supplementation in addition to lifestyle changes in children with obesity-related non-alcoholic fatty liver disease. Turk J Gastroenterol 2017; 28: 377-83